Comparative transcriptomic insights into the domestication of Pleurotus abieticola for coniferous cultivation - Sun, Lei; Sossah, Frederick Leo; Li, Yu; Sun, Huiying (Frontiers in Molecular Biosciences, 2024)
Pleurotus abieticola is a valuable edible fungus of the Pleurotaceae family with the potential for commercial cultivation. In this study, we investigated the biological characteristics, domestication, and nutritional composition of P. abieticola and explored its adaptability to coniferous substrates through transcriptomics. We optimized the growth conditions for P. abieticola mycelia and identified a suitable cultivation formula with a biological efficiency of approximately 38%. Moreover, we established that P. abieticola possesses high nutritional value. Transcriptome analysis revealed differential expression of lignocellulose-degrading enzymes and stress-resistant metabolism as key factors in the coniferous tolerance of P. abieticola. Specifically, we found significant expression of genes involved in endocytosis metabolism, indicating a vital roles in conifer adaptation. These findings provide a foundation for commercial development and subsequent strain breeding of P. abieticola, as well as for efficient utilization of conifer resources. The results of this study have important implications for the cultivation and utilization of P. abieticola as a valuable source of food and medicinal products as well as biotechnological applications.